The implementation of activity-based costing in the accountant general’s department of Malaysia - Ainol Basirah Abdul Wahab,; Muslim Har Sani Mohamad,; Julia Mohd Said, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This research aims to provide insights into the process of implementing an Activity-Based Costing (ABC) system in the Accountant General’s Department of Malaysia (AGD). Additionally, this paper examines the critical factors that influence the success of the ABC implementation process, the usefulness of the ABC system and the challenges faced during the process of implementation. Using a single case study approach, this research uses semi-structured interviews, a self-developed questionnaire survey and a documents review as methods of data collection. The findings show that the most critical factors impacting the success of ABC implementation in the AGD are related to the technicality of the ABC system during the design stage. However, findings also reveal that the ABC information derived from the ABC system has limited use. This study makes a contribution to the empirical literature on the application of the New Public Management (NPM) mechanism, particularly the adoption of a private sector management technique in the context of a public sector organization in a developing country.